Tramadol does not improve performance or impair motor function in trained cyclists - Bejder, J.; Breenfeldt Andersen, A.; Bonne, T. C.; Piil, J. F.; Hagen. L. C. H.; Dehnes, Y.; Eibye, K. H.; Nybo, L.; Nordsborg, N. B. (Medicine & Science in Sports & Exercise, 2020)
Purpose